Airdrop of Armament and Military Equipment from Aircraft - Kovačević, Dražen; Bazijanac, Ernest; Jurum-Kipke, Jasna (Promet - Traffic&Transportation, 2012)
Air supply can be performed in two ways: by transportingthe technical equipment by transport aircraft or helicopters,and unloading upon landing and by air-dropping. The airdropcan be performed by dropping without parachutes, with parachutesand by low altitude cargo extraction. In the USA- CADS(Controlled Aerial Delivery System) has been developed providingcontrol of the falling cargo via a remote controller.